Comprehensive profiles of psychological and social work factors as predictors of site-specific and multi-site pain - Jan Olav Christensen; Morten Birkeland Nielsen; Live Bakke Finne; Stein Knardahl (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVE: Despite the multifactoriality of work and health, studies of psychosocial work factors with pain are typically limited to a few factors. This study examined a wide range of factors to determine (i) typical combinations of work factor levels ("work situations") and (ii) whether "work situations" predicted pain complaints of six anatomic regions. METHODS: Questionnaires were distributed to 6175 employees twice over a two-year period. Latent profile analysis was conducted to group employees into profiles of work factor levels. Twelve work factors were measured, reflecting six themes: demands, control, role expectations, leadership, predictability, and organizational climate. Logistic and Poisson regressions compared the groups' risk of pain of the neck, head, back, shoulders, legs and arms, as well as multi-site pain (>1 pain site). RESULTS: Four latent profiles emerged based on relative levels of work factors. Profile 1 reflected relatively "desirable" levels of all factors, demonstrating the lowest risk of pain. Profile 2 exhibited the highest, and profile 3 the lowest levels of both demands and control with similar risks of pain, suggesting high levels of control were insufficient to buffer the impact of the combination of the other factors. Profile 4 exhibited "undesirable" levels of all factors and the highest risk, most notably for multi-site pain [odds ratio (OR) 2.32, 95% confidence intervals (CI) 1.80-2.85 compared with profile 1]. CONCLUSIONS: Different compositions of psychosocial exposures were differentially related to pain. Future studies should take the complexity of work into account by studying comprehensive arrays of co-occurring work factors with health.